Plausible 2005–2050 emissions scenarios project between 2 °C and 3 °C of warming by 2100. (1st February 2022) - Pielke Jr, Roger; Burgess, Matthew G; Ritchie, Justin
Abstract: Emissions scenarios used by the Intergovernmental Panel on Climate Change (IPCC) are central to climate change research and policy. Here, we identify subsets of scenarios of the IPCC's 5th (AR5) and forthcoming 6th (AR6) Assessment Reports, including the Shared Socioeconomic Pathway scenarios, that project 2005–2050 fossil-fuel-and-industry (FFI) CO2 emissions growth rates most consistent with observations from 2005 to 2020 and International Energy Agency (IEA) projections to 2050. These scenarios project between 2 °C and 3 °C of warming by 2100, with a median of 2.2 °C. The subset of plausible IPCC scenarios does not represent all possible trajectories of future emissions and warming. Collectively, they project continued mitigation progress and suggest the world is presently on a lower emissions trajectory than is often assumed. However, these scenarios also indicate that the world is still off track from limiting 21st-century warming to 1.5 °C or below 2 °C.